The future of drug industry research and the Zeneca response - U' Prichard, David C.
David C. U'Prichard and Linda M. Pullan report how Zeneca's research organization restructured itself to meet the needs of the healthcare business in 2015.
Today's drug discovery research organization must consider what the healthcare business will look like in 2015.
Increased cost pressures, more informative and expensive clinical data, and many competing drug classes require flexible, innovative research in the pharmaceutical industry. Fortunately, new tools for drug discovery and the increasing linkage of disease to specific genetic defects are enabling more efficient innovation in drug discovery. Adapting to these pressures and opportunities, Zeneca Pharmaceuticals Research changed its structure and portfolio management to ensure speed, quality and quantity in new drug discovery. New research collaborations provide new targets, technologies and drug candidates. Research projects are analyzed operationally for risk and reward, resource allocation and portfolio balance. A broader strategic review studies the disease areas and their underlying biological effects for their potential values, synergies and fit with Zeneca's business strengths.
Keywords: Drug industry research